2006
DOI: 10.1038/sj.leu.2404132
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic stem cell-derived microvesicles reprogram hematopoietic progenitors: evidence for horizontal transfer of mRNA and protein delivery

Abstract: Membrane-derived vesicles (MV) are released from the surface of activated eucaryotic cells and exert pleiotropic effects on surrounding cells. Since the maintenance of pluripotency and undifferentiated propagation of embryonic stem (ES) cells in vitro requires tight cell to cell contacts and effective intercellular signaling, we hypothesize that MV derived from ES cells (ES-MV) express stem cell-specific molecules that may also support self-renewal and expansion of adult stem cells. To address this hypothesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
1,210
0
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,436 publications
(1,239 citation statements)
references
References 42 publications
15
1,210
0
14
Order By: Relevance
“…Ambivalence was apparent for the transport and uptake categories, with most votes in the middle of the range. These results suggest perceived unmet needs across all topics, but especially in cargo loading and cargo transfer.
10.1080/20013078.2018.1535745-F0002Figure 2.EV topics about which we know the “most” [1] to the “least” [5]. Respondents were required to rank the five topics from most [1] to least knowledge [2].
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ambivalence was apparent for the transport and uptake categories, with most votes in the middle of the range. These results suggest perceived unmet needs across all topics, but especially in cargo loading and cargo transfer.
10.1080/20013078.2018.1535745-F0002Figure 2.EV topics about which we know the “most” [1] to the “least” [5]. Respondents were required to rank the five topics from most [1] to least knowledge [2].
…”
Section: Resultsmentioning
confidence: 99%
“…Respondents were required to rank the five topics from most [1] to least knowledge [2]. No rank could be used twice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been demonstrated that EVs can be derived from almost all mammalian cell types, including healthy cells21, 22 and cancerous cells 23, 24. The composition of cancer‐derived EVs (C‐EVs) is markedly changed compared to EVs from healthy cells, and C‐EVs can therefore be used as diagnostic biomarkers of cancers 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…Early work included ultrastructural studies of subcellular compartments that defined the biogenetic pathways for these particles [5,6] and the 1996 discovery that exosomes can stimulate T-cells through antigen presentation resulted in a broad increase of interest in EV research [7]. This increase in research activity was further cemented by the 2006 finding that EVs contain RNA cargoes [8,9]. The field now enjoys an exponential growth in the number of publications [10] and EVs have now been isolated from an ever-expanding array of biofluids and cell types [1].…”
Section: Introductionmentioning
confidence: 99%